Former Yugoslav Republic of Macedonia : 2013 Article IV Consultation and First Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report ;, 2013)
Conservative policies, together with external official assistance, provided Macedonia with buffers to confront spillovers from the global crisis and deal with domestic shocks. External and financial stability have been maintained despite a difficult external environment. The start of EU accession negotiations remains uncertain. Some key recommendations of earlier Article IV Consultations have been implemented; others remain outstanding. Macedonia is well positioned to return to growth, although the external outlook presents a key risk. Policies should remain focused on boosting medium-term growth.